2016
DOI: 10.18178/joaat.3.2.136-139
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Feed Supplements on Milk Yield and Milk Quality of Dairy Cattle

Abstract: This study was to evaluate the effects of feed supplements containing tannins, NPN and mineral on milk yield and milk quality of dairy cattle. Nine lactating dairy cows were designed in experiment by a completely randomized design with 3 treatments and 3 replications. Treatment consists of R0: Total Mixed Ration (TMR); RA: TMR + supplements A; RB: TMR + supplement B. The results showed that supplementation of feed supplements A and B were no effect on milk yield and quality but were had significantly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Problems associated with extended clotting time reduce the value of milk for processing. To increase the quantity of milk and improve its quality, attempts are made to modify the diet of cows [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Problems associated with extended clotting time reduce the value of milk for processing. To increase the quantity of milk and improve its quality, attempts are made to modify the diet of cows [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition affects the quality and component of milk (Tyasi et al, 2015). Moreover, milk production efficiency affected milk quality because of the efficiency of nutrient absorbtion was affected by dry matter intake (Martono et al, 2016) as well as improved forages qualities have the potential to increase milk production and milk quality (Mwendia et al, 2018). Particularly, iron contamination in bovine drinking or milk processing plant can change milk protein composition and oxidation in the final milk product, which decreases the quality and nutritional value of milk (Wang et al, 2016).…”
Section: Quality Of Milkmentioning
confidence: 99%
“…A study by Rofiq and Gorgulu (2014) demonstrated that the combination of cloves and orange peel in a dairy total mixed ration played an antagonistic role in reducing digestion. Martono et al (2016) reported that combining different feed supplements could increase feed efficiency in dairy cattle. However, no relevant literature has been found regarding the combined effect of M. oleifera and mulberry supplementation.…”
Section: Introductionmentioning
confidence: 99%